A dual‐band efficient circularly polarized rectenna for RF energy harvesting systems. Issue 1 (21st December 2018) - Jie, Ang M.; Nasimuddin, N.; Karim, Muhammad F.; Chandrasekaran, Karthik T.
Abstract: A multilayered circularly polarized (CP), dual‐band, stacked slit‐/slotted‐patch antenna with compact size and with compact rectifier is offered for RF energy harvesting systems. The compact dual‐band CP antenna size is able to achieve by stacking slotted‐circular‐patch (SCP) on the substrate above the tapered‐slit‐octagon patch (TSOP). Dual‐band CP radiation is realized by stacking the SCP on the TSOP and the microstrip feedline with metallic‐via to SCP. Eight‐tapered‐slit with length difference of 6.25% are embedded along the octagonal directions symmetrically on the TSOP from the patch's center and two unequal size circular slots are embedded in diagonal axis onto SCP to produce dual‐orthogonal modes with almost equal magnitude for CP waves. The designed antenna is realized measured gain of greater than 5.2 dBic across the band (0.908‐0.922 GHz) with maximum gain of 5.41 dBic at 0.918 GHz and gain of greater than 6.14 dBic across the band (2.35‐2.50 GHz) with maximum gain of 7.94 dBic at 2.485 GHz. An overall antenna volume is 0.36 λ o  × 0.36 λ o  × 0.026 λ o ( λ o is free space wavelength at 0.9 GHz). A compact composite right‐/left‐handed (CRLH) based rectifier with dual‐band at 0.9 and 2.45 GHz is designed, prototyped, and measured. The right‐handed (RH) part of the CRLH transmission line (TL) is formed by a microstrip line. The left‐handed (LH) part of the CRLH‐TL is formed by lumped components. The measured RF‐DC conversion efficiency is 43% at 0.9 GHz and 39% at 2.45 GHz with rectifier size of 0.18 λ o  × 0.075 λ o  × 0.0002 λ o at 0.9 GHz.